Aussendienst : Kunstprojekte in öffentlichen Räumen Hamburgs Mai 2000- Mai 2002 - Schmidt-Wulffen, Stephan; Babias, Marius; Könneke, Achim; Lanz, Stephan; Stad Hamburg (Freiburg : modo Verlag, 2002)
Aagaard Andersen, Jeppe ; Bonvicini, Monica ; Chicks on Speed ; Brinkmann, Thomas ; Dejanov, Plamen ; Dittmer, Peter ; Ecker, Bogomir ; Gabriel, Ulrike und David ; Giese, Tita ; Gillick, Liam ; Haaning, Jens ; Hahn, Felix ; Heger, Swetlana ; van Houwelingen, Hans ; Jones, Ronald ; Kern, Stefan ; Knowbotic Research ; Kubin, Felix ; Nicolai, Carsten ; Pernice, Manfred ; Pflumm, Daniel ; Rimbaud, Robin ; Ruzicska, Bernd ; Sander, Katya ; Schäfer, Christoph ; Scher, Julia ; Signer, Roman ; Spitzer, Serge ; Stricker, Thomas ; Tan, Fiona ; Yui, Miki
Duits & Engels
boek
Keywords: Hamburg